Malocclusion prevalence in 11-13 years old student in the Madrasah Tsanawiyah Melirang, Gresik - Ardani, I Gusti Wahju Aju; Rahmawati, Dwi; Nugraha, Alexander Patera; Pramusita, Adya; Ariyadi, Satrio Kris (Faculty of Dental Medicine Universitas Airlangga, 2024)
Background: When teeth are not positioned correctly, it is referred to as malocclusion, and it frequently happens in the general population. One of the traits of malocclusion that is frequently observed in children beginning in the early mixed dentition phase is crowded teeth. This disorder will become more serious and cause speech, masticatory, and cosmetic issues if therapy is not started right away. Environmental and genetic factors have a significant impact on malocclusion. Therefore, a child's nutrition, bad habits, trauma to the main teeth, and the pattern acquired from both parents will all affect the malocclusion's characteristics. Purpose: Enhance instruction in identifying malocclusion and the stages of permanent and changing tooth growth. Methods: Forty-six students from Madrasah Tsanawiyah's classes 7A and 7B participated. Intraoral examinations and the completion of pretest and posttest questionnaires were used to collect data. Next, Stastical Package Social Science (SPSS) version 23 was used to analyze the frequency distribution data. Results: Male students had more crowded teeth (20) and less crowded teeth (2) than female students (18) and less crowded teeth (6). Class I malocclusion (41), class II malocclusion (3), and class III malocclusion (2) are the highest. Conclusion: Malocclusion class I is characterized by the greatest number of crowded teeth in males aged 8 to 10 years.